Smartphone use among young drivers: Applying an extended Theory of Planned Behaviour to predict young drivers' intention and engagement in concealed responding. (January 2022) - Eren, Hazal; Gauld, Cassandra
Highlights: Responding in a concealed manner on a smartphone is prevalent among young drivers. The Theory of Planned Behaviour standard constructs predicted this behaviour. Anticipated action regret, and problematic phone use also predicted this behaviour. Different salient beliefs for high and low intenders to engage in this behaviour. Findings can be used to create public education messages targeting this behaviour. Abstract: Young drivers, aged 17–25 years, are more likely than other age groups to access social interactive technologies (e.g., Snapchat, Facebook) on their smartphones while driving. Many of these young drivers do so in a concealed manner, thereby diverting their eyes from the road for extended periods and increasing their crash risk. In accordance with previous research, an extended Theory of Planned Behaviour (TPB) was applied in this survey study to investigate psychosocial predictors of young drivers' intention, and behaviour, of responding to social interactive technology on a smartphone in a concealed manner. Participants ( N  = 154) resided in Australia, were aged 17–25 years, owned a provisional or an open licence, and owned a smartphone. Participants completed two online surveys administered 1-week apart. The first survey measured intention and assessed the TPB standard constructs of attitude, subjective norm, and perceived behavioural control, as well as the additional constructs of anticipated action regret, anticipated inaction regret, and problematic mobile phone usage. The first survey also assessed whether there were any differences in the salient beliefs (elicited in a previous study) about smartphone use between high and low intenders to engage in this behaviour. The second survey measured engagement in the behaviour of responding in a concealed manner in the previous week. Hierarchical multiple regression analyses showed the standard TPB accounted for 69% of variance in intention, and a further 4% was accounted for by the extended constructs. In the final model, all variables, except anticipated inaction regret, were significant predictors of intention. Intention was the only significant predictor of behaviour. A series of MANOVAs found significant differences in the salient belief items between high and low intenders (e.g., high intenders were more likely to believe that friends/peers and other drivers would approve of them engaging in this behaviour). These key findings can be used as focal points for public education messages to persuade young drivers to reduce the frequency of their smartphone use, which is vital to improve road safety for all users.